Steam generation with stoichiometric combustion of H2/O2 as a way to simultaneously provide primary control reserve and energy storage. (1st November 2017) - Stathopoulos, P.; Sleem, T.; Paschereit, C.O.
Highlights: Energy storage and back conversion by H2 /O2 combustion, electrolysis and steam plants. Combination of primary control reserve with steam power plants and electrolysis storage. The combined system is economically viable without any incentives. High sensitivity of the economic performance on PCR and electricity prices. High economic potential for systems with energy surplus and renewables. Abstract: Energy storage and its combination with electric network services is a major issue in networks with a high percentage of variable renewables. Among the many energy storage options very few are commercially available and economically viable. The current work presents a method to combine electrolytic hydrogen energy storage with steam power plants, with the aim to provide primary control reserve. The key component is a steam generator that burns stoichiometric mixtures of H2 and O2 to produce steam. The product gas is directly injected in the steam cycle of a coal power plant to increase its power. The integration of this particular steam generator in the steam cycle is evaluated thermodynamically and the economic performance of the whole system (electrolysis, gas storage and steam generator) is subsequently presented. It is demonstrated that the proposed system is a viable alternative for energy storage and primary control reserve. Especially when the levelized cost of electricity of a coal power plant is paid for the electrolysis electricity consumption, the proposed system becomes a viable option for large scale energy storage. In conclusion, it is shown that electricity prices and the price of primary control reserve have the strongest influence on the economic viability of the system.